Human Resource Management Affecting Work Efficiency of the Automotive and Auto Parts Industry - เอนกศักยพงศ์, กรสรรค์; ยาวิราช, เนตร์พัณณา (RMUTT Global Business and Economics Review, 2014)
The purposes of this research were (1) to study human resource management, working morale, and work efficiency of the automotive and auto parts industry, (2) to explore the relationships among human resource management, working morale, and work efficiency, and (3) to investigate the effects of human resource management and working morale on work efficiency. The samples were 369 staff who were working in the automotive and auto parts factories in PathumThani. The research instrument was the questionnairewhile statistics used for data analysis included confirmatory factor analysis (CFA) and Structural Equation Modeling (SEM).The results revealed that 1) the levels of opinion of human resource management ranged from medium level to high level, 2) the result of the relationships indicated that all variables were related at high level (r = 0.752), and 3) the structural models of human resource management and morale in job performance affected work efficiency Chi-square = 53.339, p-value = 0.031, df = 36, GFI = 0.977, and RMSEA = 0.036. Besides, human resource management and working morale had the direct effect on work efficiency with weight parameters of the effects equaled to 0.36 (p = 0.041) and 0.61 (p = 0.001), respectively.